Foreign Investment in Southeast Asia: the Role of Political Stability, Trade Openness, Regulatory Quality, and Gross Domestic Product (2014–2023) - Muhammad Fariz; Nur Hidayah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Foreign Direct Investment (FDI) plays a crucial role in promoting economic growth and development, particularly in developing regions such as Southeast Asia. This study aims to analyze the determinants of FDI by examining the effects of institutional and macroeconomic factors, namely political stability, regulatory quality, trade openness, and Gross Domestic Product (GDP) across 11 Southeast Asian countries during the period 2014–2023. Unlike previous studies that typically focus on limited variables or a single country, this research employs a panel data approach across countries and time to provide a more comprehensive analysis. The analytical method used is panel data regression with Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with the best model selected through Chow, Hausman, and Lagrange Multiplier tests. The results indicate that trade openness and GDP have a positive and significant effect on FDI, confirming that market size and international trade integration are key factors in attracting foreign investment. Meanwhile, political stability and regulatory quality do not have a significant effect on FDI.